Hasil analisis sefalometri metode ricketts pasien ortodonti rsgm usakti pada tahun 2021-2022 - Nakia Mutiara Insani Riyanto; Yuniar Zen (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Ricketts analysis is a commonly used cephalometry analysis for treatment plans and research. Purpose: The objective of this research is to see the overall picture of cephalometric analysis using Ricketts analysis. Methods: This research applies a descriptive observational in cross sectional design. The samples’ lateral cephalograms are taken from orthodontic patients at RSGM FKG Usakti in 2021-2022. The analysis was executed by measuring 10 Ricketts analysis parameters. Results: The results shows that the mean value of each parameters were the angle of the facial axis is 88°, facial depth 89°, mandibular plane 22°, convexity of point A 3.6 mm, angle of the lower incisor to the A-Pg plane 31°, distance of the lower incisor to the A-Pg plane 4.7 mm, distance of the upper molar to PtV 18 mm, distance of the lower lip to the E line 2.6 mm, palatal plane to FHP 1,4°, and distance of the upper lip to the E line 2 mm. Conclusion: Orthodontic patients who visited RSGM FKG Usakti in 2021-2022 showed that the majority of the patients had a facial axis of 88º, a facial depth of 89º, a mandibular plane of 22º, a convexity of point A of 3.4 mm, a palatal-FHP plane of 1,4º, the position of the lower incisors is proclination (angle 31º) and protrusive anteriorly (distance 4.7 mm), the position of the molars is 18 mm, the position of the upper lip is 2 mm in front of the E line and the lower lip is 2.6 mm in front of the E line which shows that both lips are classified as protrusion.